Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Re-examining dam's impact on fish habitats from a novel hydrological perspective: Implication for river habitat protection and restoration - Jianfei Wu; Qiang Liu; Liqiao Liang; Xiaofeng Xu; Xuan Wang; Ran Li; Yuting Yang; Tao Sun; Chunhui Li; Jifa Qin (Journal of Environmental Management, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

The impact on greenhouse gas emissions of damming the rivers in China from 1960 to 2060 - Xincong Liu; Ran Fang; Yaqin Jiang; Shan Chen; Xiehang Chen; Hengyu Pan; Hongqiao Chen; Qiang Ma; Li Zeng (Journal of Cleaner Production, 2026)

Boosting CO2 photoreduction with Ta doped Bi4NbO8Cl via polarization induced charge separation - Ran Dian; Min Li; Zhiheng Li; Jun Wu; Xinyu Huang; Xinhao Xu; Wenfu Xie; Tianyu Zhang; Qiang Wang (Journal of Environmental Sciences, 2026)

Association between polymorphisms in AKR1C2 gene and litter size traits in Xiang pigs - Lan Wang; Xia Chen; Mingchuan Guo; Fenfang Qi; Jian Li; Yaxue Liu; Xi Niu; Qiang Wang; Xueqin Ran; Jiafu Wang (Animal Reproduction Science, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

AjFOSL Modulates Cell Cycle-Related Genes Associated with Coelomocyte Regeneration in Apostichopus japonicus Evisceration - Ran Xiao; Yinan Wang; Xiaoli Xu; Jiong Wu; Qiang Li (Fishes, 2026)
Apostichopus japonicus undergoes evisceration in response to adverse environmental stimuli, and its coelomocytes undergo rapid regeneration within 6–24 h to restore innate immune function. FOS, an immediate early gene, regulates cell proliferation and cycle, but its role in A. japonicus coelomocyte regeneration after evisceration is unclear. In this study, AjFOSL from A. japonicus was cloned, which harbors a 609 bp open reading frame (ORF) encoding 202 amino acids (aa) with a conserved bZIP domain and is localized on chromosome 14. It shares 58% homology with FOS from Holothuria leucospilota and Lytechinus pictus. Phylogenetic analysis revealed that AjFOSL clusters closely with FOS from Magallana gigas and Mytilus edulis. Tissue distribution analysis showed that AjFOSL was widely expressed in various tissues, with the highest expression level detected in the tentacles. Temporal expression profiling demonstrated that AjFOSL was significantly upregulated by 1.75-fold at 6 h after evisceration. After AjFOSL knockdown, the peak expression of Cyclin A, Cyclin B, and E2F was delayed and the coelomocyte number was consistently reduced compared with that in the evisceration-only group. The AjFOSL acted as an immediate early response gene and was associated with the regulation of coelomocyte regeneration by modulating the expression of cell cycle-related genes. This study provides novel insights into the molecular associations underlying coelomocyte regeneration and the evolutionary adaptation of FOS genes in echinoderms.

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Effects of industrial solid wastes on the rheological behavior and electrical resistivity-acoustic emission responses of cement-based grouted bodies under loading - Xinchao Zheng; Qiang Sun; Fang Liu; Yuhang Li; Boxing Yang; Ran Tang (Journal of Environmental Management, 2026)

Late Mesozoic exhumation of metamorphic core complexes from the Xiaoqinling to Dabie orogen, central China: a record of Paleo-Pacific slab rollback - Wan-Shan Lei; Yu Duan; Zhi-Qiang Liu; Ran Wang; Hai-Dong Zhang; San-Zhong Li (International Geology Review, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Comparative plastomes and phylogenetic relationships of Breynia, Glochidion, Phyllanthus, Sauropus, and Synostemon from plastomes and ITS - Ran Wei; Qiang Li (Genetica, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Ni/Zr co-doping strategy to promote cyclic performance of CaO-based materials for thermochemical energy storage: Experimental and first-principles insights - Zhu-yu Li; Le-ran Li; Jing-yi Liu; Qi Niu; Zhi-mo Fang; Ji-hong Li; Kai Li; Qiang Lu (Chemical Engineering Journal, 2025)

Operational optimisation of domestic refrigerators based on user behaviour prediction and deep reinforcement learning - Hao-Ran Li; Wei Zhang; Qiang Chen (International Journal of Refrigeration, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Ecological stoichiometry of carbon, nitrogen, phosphorus, and silicon in coastal salt marsh plants and its implications for carbon sink management - Xinyu Zhang; Zhaoliang Song; Yuntao Wu; Lele Wu; Qiang Li; Qian Hao; Shaopan Xia; Yidong Wang; Xiangbin Ran; Yunying Fang; Hailong Wang (Journal of Environmental Management, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

“Using waste straw to prevent pollution”: Enabling closed-loop design of chrome-free tanning agent with tanning-masking dual effect - Huaqing Liu; Taotao Qiang; Ran Zhang; Ruilong Li; Xin Sun; Sijie Yu; Chao Wu; Longfang Ren (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Pillar[5]arene@AuNP-Functionalized, Magnetically-Propelled Helical Micromotors for On-The-Fly Electrochemical Biosensing of p53 DNA Sequence - Zhiyong Ran; Yue Li; Xiankun Lin; Qiang He (Chemical Engineering Journal, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

Improving the understanding of rainfall-runoff processes: Temporal dynamic of event runoff response in Loess Plateau, China - Qiang Wu; Tianning Xie; Chengshuai Liu; Wenzhong Li; Li Zhang; Guang Ran; Yuanhao Xu; Yehai Tang; Zhenyue Han; Caihong Hu (Journal of Environmental Management, 2025)

Insight into the molecular structure construction and pyrolysis mechanism simulation of typical carbonaceous feedstocks for the rapid design and preparation of porous carbon-based materials - Li Zhao; Bo Yuan; Lele Gong; Hongwei Wang; Qiansong Ran; Lingyan Qin; Jiaqi Liu; Luchao Zhang; Kai Li; Guojie Liang; Li Li; Qiang Xie (Fuel, 2025)

Enhanced thermochemical heat storage performance of CaO/CaCO3 via pyroligneous acid impregnation and Co/Mn co-doping - Zhu-yu Li; Le-ran Li; Sheng Li; Ding-can Wang; Qi Niu; Kai Li; Ji Liu; Qiang Lu (Chemical Engineering Journal, 2024)

Suitable water management improving cold tolerance of rice seedlings - Qiang Zhang; Feng Wen; Bingbing Li; Zhi Li; Zhenjiang Wu; Xu Kuang; Guilong Yu; Xiangchen Liu; Yang Hu; Yuchen Zhang; Ran Yu; Lingling Ding; et al. (Cereal Research Communications, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Organic matter composition and stability in estuarine wetlands depending on soil salinity - Lele Wu; Zhaoliang Song; Yuntao Wu; Shaopan Xia; Yakov Kuzyakov; Iain P. Hartley; Yunying Fang; Changxun Yu; Yidong Wang; Ji Chen; Laodong Guo; Zimin Li; et al. (Science of The Total Environment, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Associations of long-term exposure to low-level PM2.5 and brain disorders in 260,922 middle-aged and older adults - Ne Qiang; Yujia Bao; Yongxuan Li; Na Zhang; Yanqiu Zhou; Xiaobei Deng; Lefei Han; Jinjun Ran (Chemosphere, 2024)

Mo6+ bifunctional substitution of P2-type manganese oxide for high performance sodium-ion batteries - Lincai Xu; Qiang Hu; Qiwen Ran; Lei Li; Gan Cai; Haijiao Xie; Xingquan Liu (Chemical Engineering Journal, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Dietary Bacillus velezensis T23 fermented products supplementation improves growth, hepatopancreas and intestine health of Litopenaeus vannamei - Hongwei Yang; Dongdong Du; Qingshuang Zhang; Tsegay Teame; Anran Wang; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Shengkang Li; et al. (Fish & Shellfish Immunology, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Mechanical characteristics and stability analysis of an innovative type of steel–concrete composite support in shallow-buried excavation tunnels - Yuan Song; Changbai Wang; Mingli Huang; Ran Li; Qiang Wang (Tunnelling and Underground Space Technology, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Revisiting the physical processes controlling the tropical atmospheric circulation changes during the Mid-Piacenzian Warm Period - Ke Zhang; Yong Sun; Zhongshi Zhang; Christian Stepanek; Ran Feng; Daniel Hill; Gerrit Lohmann; Aisling Dolan; Alan Haywood; Ayako Abe-Ouchi; Bette Otto-Bliesner; Camille Contoux; et al. (Quaternary International, 2024)

The accumulation and carbon sequestration potential of biogenic silica in coastal salt marshes: Implications for relative sea-level rise - Xiangwei Zhao; Xiaodong Zhang; Zhaoliang Song; Lukas Van Zwieten; Xiangbin Ran; Yulin Pu; Jun Sun; Qiang Li; Lele Wu; Xiaomin Yang; Yuqiu Wei; Zimin Li; et al. (CATENA, 2024)

High fat diet-induced downregulation of TRPV2 mediates hepatic steatosis via p21 signalling - Pengfei Wei; Lixuan Li; Chenqiu Ran; Mingyue Jin; Huijuan Zhao; Kelaier Yang; Yu Wang; Huaqiu He; Mengyang Jia; Hongyan Pan; Qiang Li; Jing Guo (Journal of Physiology and Biochemistry, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Efficient rhodamine B dye degradation by red mud-grapefruit peel biochar catalysts activated persulfate in water - Shuman Deng; Maolin Yang; Qiang An; Zheng Li; Bin Zhao; Binbin Ran (Environmental Science and Pollution Research, 2023)

Dietary cultured supernatant mixture of Cetobacterium somerae and Lactococcus lactis improved liver and gut health, and gut microbiota homeostasis of zebrafish fed with high-fat diet - Shenghui Li; Hongwei Yang; Ya Jin; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Chenglong Wu; Shengkang Li; Kaimin Cheng; et al. (Fish & Shellfish Immunology, 2023)

Deep transfer learning based on transformer for flood forecasting in data-sparse basins - Yuanhao Xu; Kairong Lin; Caihong Hu; Shuli Wang; Qiang Wu; Li Zhang; Guang Ran (Journal of Hydrology, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

OsBBX19-OsBTB97/OsBBX11 module regulates spikelet development and yield production in rice - Abdullah Shalmani; Uzair Ullah; Li Tai; Ran Zhang; Xiu-Qing Jing; Izhar Muhammad; Nadeem Bhanbhro; Wen-Ting Liu; Wen-Qiang Li; Kun-Ming Chen (Plant Science, 2023)

Crystallographic oriented plating by using lithiophilic ionic additives in carbonate electrolyte for enabling high voltage lithium metal batteries - Qiwen Ran; Jintao Liu; Lei Li; Qiang Hu; Fuquan Nie; Hongyuan Zhao; Xingquan Liu (Chemical Engineering Journal, 2023)

Current and future potential soil organic carbon stocks of vegetated coastal ecosystems and their controls in the Bohai Rim Region, China - Shaobo Sun; Zhaoliang Song; Baozhang Chen; Yidong Wang; Xiangbin Ran; Yunying Fang; Lukas Van Zwieten; Iain P. Hartley; Yafei Wang; Qiang Li; Lele Wu; Cong-Qiang Liu; et al. (CATENA, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Specific PhytOC fractions in rice straw and consequent implications for potential of phytolith carbon sequestration in global paddy fields - Xiaomin Yang; Zhaoliang Song; Laodong Guo; Jingxu Wang; Yilun Ni; Zimin Li; Qian Hao; Qiang Li; Lele Wu; Wei Kuang; Yang Liu; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Maximum displacement prediction of composite floor system under falling impact - Jing-Zhou Zhang; Guo-Qiang Li; Ying-Zhi Sun; Jing Sun; Zhi-Wei Yu; Ran Feng (Engineering Structures, 2023)

Efficient electrocatalytic reduction of CO2 to CO on highly dispersed Ag nanoparticles confined by Poly(ionic liquid) - Guo-Yi Duan; Xiao-Qiang Li; Yi-Ran Du; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Cationic molecular probes based on aggregation-induced emission for fluorescent sensing and super-resolution imaging of insulin fibrosis - Li-Jun Mei; Cheng Fan; Chu-Ran Xu; Qi Yu; Chong Li; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2023)

Storage, patterns and influencing factors for soil organic carbon in coastal wetlands of China - Shaopan Xia; Zhaoliang Song; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Weiqi Wang; Qiang Li; Iain P. Hartley; Yuanhe Yang; Hongyan Liu; Yidong Wang; Xiangbin Ran; et al. (Global Change Biology, 2022)
Soil organic carbon (SOC) in coastal wetlands, also known as “blue C,” is an essential component of the global C cycles. To gain a detailed insight into blue C storage and controlling factors, we studied 142 sites across ca. 5000 km of coastal wetlands, covering temperate, subtropical, and tropical climates in China. The wetlands represented six vegetation types ( Phragmites australis , mixed of P. australis and Suaeda , single Suaeda , Spartina alterniflora , mangrove [ Kandelia obovata and Avicennia marina ], tidal flat) and three vegetation types invaded by S. alterniflora ( P. australis , K. obovata , A. marina ). Our results revealed large spatial heterogeneity in SOC density of the top 1‐m ranging 40–200 Mg C ha −1 , with higher values in mid‐latitude regions (25–30° N) compared with those in both low‐ (20°N) and high‐latitude (38–40°N) regions. Vegetation type influenced SOC density, with P. australis and S. alterniflora having the largest SOC density, followed by mangrove, mixed P. australis and Suaeda , single Suaeda and tidal flat. SOC density increased by 6.25 Mg ha −1 following S. alterniflora invasion into P. australis community but decreased by 28.56 and 8.17 Mg ha −1 following invasion into K. obovata and A. marina communities. Based on field measurements and published literature, we calculated a total inventory of 57 × 10 6 Mg C in the top 1‐m soil across China's coastal wetlands. Edaphic variables controlled SOC content, with soil chemical properties explaining the largest variance in SOC content. Climate did not control SOC content but had a strong interactive effect with edaphic variables. Plant biomass and quality traits were a minor contributor in regulating SOC content, highlighting the importance of quantity and quality of OC inputs and the balance between production and degradation within the coastal wetlands. These findings provide new insights into blue C stabilization mechanisms and sequestration capacity in coastal wetlands.

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

The effect and attributable risk of daily temperature on category C infectious diarrhea in Guangdong Province, China - Qiang Hao; Qi Gao; Ran Zhao; Haitao Wang; Hao Li; Baofa Jiang (Environmental Science and Pollution Research, 2022)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

miR-19a mitigates hypoxia/reoxygenation-induced injury by depressing CCL20 and inactivating MAPK pathway in human embryonic cardiomyocytes - Qiang Fu; Tao-Ran Mo; Xiao-Yang Hu; Yin Fu; Ji Li (Biotechnology Letters, 2021)

The Mechanism of Trivalent Inorganic Arsenic on HIF-1α: a Systematic Review and Meta-analysis - Jiaqing Liu; Qiang Niu; Yunhua Hu; Shanshan Ran; Shugang Li (Biological Trace Element Research, 2020)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

RNA-Seq-based transcriptomic profiling of primary interstitial cells of Cajal in response to bovine viral diarrhea virus infection - Shengnan Li; Xinyan Hu; Ruixin Tian; Yanting Guo; Junzhen Chen; Zhen Li; Xinyan Zhao; Ling Kuang; Duoliang Ran; Hongqiong Zhao; Xiaohong Zhang; Jinquan Wang; et al. (Veterinary Research Communications, 2019)

Genome-wide identification, expression, and interaction analysis for ovate family proteins in peach - Huifeng Li; Qinglong Dong; Xiaoping Zhu; Qiang Zhao; Kun Ran (Molecular Biology Reports, 2019)

Genome-wide identification, expression profiling, and protein-protein interaction properties of ovate family proteins in apple - Huifeng Li; Qinglong Dong; Qiang Zhao; Kun Ran (Tree Genetics & Genomes, 2019)

Post-disaster assessment of 2017 catastrophic Xinmo landslide (China) by spaceborne SAR interferometry - Keren Dai; Qiang Xu; Zhenhong Li; Roberto Tomás; Xuanmei Fan; Xiujun Dong; Weile Li; Zhiwei Zhou; Jisong Gou; Peilian Ran (Landslides, 2019)

An Evaluation of the Resilience of the Regional Agricultural Water and Soil Resource System in Heilongjiang Province, China - Dong Liu; Ran Mu; Qiang Fu; Chunlei Liu; Tianxiao Li; Khan M. Imran; Song Cui; Faiz M. Abrar (Agricultural Research, 2018)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Bioinformatic identification and expression analysis of the Malus domestica DREB2 transcription factors in different tissues and abiotic stress - Huifeng Li; Qiang Zhao; Xiaoli Sun; Houzhen Jia; Kun Ran (Journal of Plant Biochemistry and Biotechnology, 2017)

C-myc overexpression drives melanoma metastasis by promoting vasculogenic mimicry via c-myc/snail/Bax signaling - Xian Lin; Ran Sun; Xiulan Zhao; Dongwang Zhu; Xueming Zhao; Qiang Gu; Xueyi Dong; Danfang Zhang; Yanhui Zhang; Yanlei Li; Baocun Sun (Journal of Molecular Medicine, 2017)

Field monitoring of groundwater responses to heavy rainfalls and the early warning of the Kualiangzi landslide in Sichuan Basin, southwestern China - Qiang Xu; Hanxiang Liu; Jiaxin Ran; Wenhui Li; Xu Sun (Landslides, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

The biochemical and immunological characterization of two serpins from Clonorchis sinensis - Huali Lei; Yanli Tian; Wenjun Chen; Xiaoyun Wang; Xuerong Li; Qiang Mao; Jiufeng Sun; Ran Li; Yanquan Xu; Chi Liang; Yan Huang; Xinbing Yu (Molecular Biology Reports, 2013)

Toxicity of CdTe QDs with different sizes targeted to HSA investigated by two electrochemical methods - Zi-Qiang Xu; Lu Lai; Dong-Wei Li; Ran Li; Chen Xiang; Feng-Lei Jiang; Shao-Fa Sun; Yi Liu (Molecular Biology Reports, 2013)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)

CLOCK/BMAL1 regulates human nocturnin transcription through binding to the E-box of nocturnin promoter - Ran Li; Jiping Yue; Yu Zhang; Lan Zhou; Wei Hao; Jiangang Yuan; Boqin Qiang; Jian M. Ding; Xiaozhong Peng; Ji-Min Cao (Molecular and Cellular Biochemistry, 2008)